TASARRUFUN İPTALİ DAVASINDA TİCARİ İŞLETME DEVRİ KARİNESİ - (:unkn) unknown (My University, 2013)
Tasarrufun iptali davaları alacaklıların menfaatine hizmet etmektedir. Zarar verme kastından dolayı iptal başlığını taşıyan İİK m.280 ise genel hükümdür. Bu yüzden diğer iki maddeye nazaran sıkı şartlara bağlanmıştır ve uygulanması en zor olan hükümdür. İptal davalarında ispat faaliyeti güçlük oluşturduğundan Mehaz İsviçre Hukukunda bir kısım kanuni karineler oluşturulmuştur. Türk kanun koyucu Zarar verme kastından dolayı iptal hükmünde Mehaz İsviçrede öngörülmemiş olan ticari işletmenin devrine ilişkin bir karine eklemiştir. Bu karine ticari hayatta işlemleri tehdit etmektedir.

Action for rescission of disposition is for creditors interest. According to enforcement law the action for rescission owing to the intention to damage is a general rule. In this area, two more specific rules are present. Among these three rules the general one has more strict requirements and practicing it is the hardest. In Swiss law which is the origin of Turkish law, the rule maker created some presumptions to facilitate the evidence. However, in Turkish law the rule maker created another presumption for the transaction of companies. This presumption endangers the reliability of the operation in the market.
The presumption for the transaction of companies in actio pauliana
Keywords: Hukuk